Harnessing titanium dioxide surface toward novel functional materials - Solera-Rojas, José A. (2016)
The ever-increasing worldwide energy consumption has led the society to quest for novel and functional materials that can be used in the development of solar fuels to some extent lessen the dependence on fossil fuels. In this context, the role of titanium dioxide has been investigated to generate versatile materials able to harness the light emitted by the Sun. Thus, the main research avenues of such semiconductor oxide are focus on dye-sensitized solar cells (DSSCs) and photoelectrochemical cells for the oxidation of water molecule. Indeed, the modification of the semiconductor oxide surface by band-gap engineering greatly enhances its optical properties and catalytic activity. In this review, we address some fundamental issues regarding structural, optical and electronic properties that render TiO2 a versatile substrate in surface chemistry, and as entry for anchoring and functionalization strategies for the development of solar cell devices and catalytically active surfaces.